Identification of key sequence features required for microRNA biogenesis in plants - Rojas, Arantxa M. L. (Nat Commun, 2020)
MicroRNAs (miRNAs) are endogenous small RNAs of ∼21 nt that regulate multiple biological pathways in multicellular organisms. They derive from longer transcripts that harbor an imperfect stem-loop structure. In plants, the ribonuclease type III DICER-LIKE1 assisted by accessory proteins cleaves the precursor to release the mature miRNA. Numerous studies highlight the role of the precursor secondary structure during plant miRNA biogenesis; however, little is known about the relevance of the precursor sequence. Here, we analyzed the sequence composition of plant miRNA primary transcripts and found specifically located sequence biases. We show that changes in the identity of specific nucleotides can increase or abolish miRNA biogenesis. Most conspicuously, our analysis revealed that the identity of the nucleotides at unpaired positions of the precursor plays a crucial role during miRNA biogenesis in Arabidopsis.